Odpowiedzi

  • Użytkownik Zadane
2010-01-10T14:21:45+01:00
A)
4y-x=6 x=-6
17y=0 y=0
ROZWIAZANIE:
4y-x=6
x=6
4y-6=6
x=6
4y=6+6
x=6
4y=12/4
x=6
y=3
x=6

17y=0
y=0
17*0=0
y=0
0=0
y=0

2010-01-10T14:23:31+01:00
A)
4y-x=6 /*(-1) x=-6
17y=0 y=0

-4y+x=-6
17y=0

x=-6+4y
17y=0 /:17

y=0
x=-6+0

y=0
x=-6



d)
3r=s r=4
3r+s=24 s=12


s=3r
s+s=24

2s=24 /:2
s=3r

s=12
3r=12/:3

s=12
r=4



b)
a=b a=3
2a+b=9 b=3

2a+a=9
a=b

3a=9/:3
a=b

a=3
b=3

Najlepsza Odpowiedź!
2010-01-10T14:35:23+01:00
A) 4y-x=6
17y=0 /17

4y - x = 6
y = 0

4 * 0 - x = 6
y = 0

- x = 6 / * (-1)
y = 0

x = -6
y = 0

b) a=b
2a+b=9

a = b
2 * b + b = 9

a = b
2b + b = 9

a = b
3b = 9 / : 3

a = b
b = 3

a = 3
b = 3

c) u=4v
5u-v=10

u = 4v
5 * (4v) - v = 10

u = 4v
20 v - v = 10

u = 4v
19v = 10 /:19

u = 4v
v = 10/19

u = 4 * 10/19
v = 10/19

u = 40/19
v = 10/19

d) 3r = s
3r+s = 24


s = 3r
s+s = 24

2s = 24 /:2
s = 3r

s = 12
3r = 12/:3

s = 12
r = 4